Aesthetic Education as an Important Factor of Spiritual Development - Tugalov Ismat Khatomovoich (Zien Journals, 2022)
The article discusses the aesthetic component of education in its basic meaning for the formation of the spiritual culture of the individual.
Keywords: education; art; harmony; morality